FeOOH electrodeposited on Ag decorated ZnO nanorods for electrochemical energy storage. Issue 45 (19th April 2016) - Yang, Sainan; Li, Yiju; Xu, Tengfei; Li, Yuguang; Fu, Huiqun; Cheng, Kui; Ye, Ke; Yang, Long; Cao, Dianxue; Wang, Guiling
Abstract : In this work, an FeOOH/Ag/ZnO shell/core array electrode was prepared by electro-depositing FeOOH on Ag decorated ZnO nanorod arrays, and found to be suitable as an electrochemical energy storage material. Abstract : In this work, an FeOOH/Ag/ZnO shell/core array electrode was prepared by electro-depositing FeOOH on Ag decorated ZnO nanorod arrays. Some characterization methods, including X-ray diffraction analysis, X-ray photoelectron spectroscopy, scanning electron microscopy and transmission electron microscopy were used to study the structure and surface morphologies of FeOOH/Ag/ZnO. The results suggest that Ag particles are homogeneously distributed on ZnO nanorods, and FeOOH is well-distributed on the surface of Ag/ZnO nanorod arrays. When evaluated as a supercapacitor electrode material, the FeOOH/Ag/ZnO shell/core array electrode exhibits a high specific capacitance of 376.6 F g −1 at a charge/discharge current density of 1 A g −1, and 70.3% specific capacitance is retained after 1000 cycles. The superior pseudo-capacitive properties of FeOOH/Ag/ZnO shell/core arrays are attributed to the unique shell/core structure. First, the ZnO nanorod arrays as skeleton loading active materials can provide a large surface to volume for easy access of electrolyte ions. Second, the Ag decorated on ZnO nanorods can improve the electrical conductivity of the as-prepared electrode, which can provide fast electron transfer for faradaic reactions. The results confirm that FeOOH/Ag/ZnO shell/core arrays are advantageous as electrochemical energy storage materials.